The Role of Cytokines in Inflammatory Bowel Disease - G. Radford-Smith; D. P. Jewell (Mediators of Inflammation)
Cytokines play an important role in the development and persistence of the inflammatory lesions seen in Crohn's disease and ulcerative colitis. This review discusses the current thinking of the role of cytokines in chronic intestinal inflammation including the involvement of immunoregulatory cytokines within the Th1 and Th2 subsets.